Pembuatan Model Kendali Mutu Data Sedimen - Sri Mulat Yuningsih; Asep Ferdiansyah; Muhammad Fauzi (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2018)
Special treatment for watershed management was needed due to severe of watershed condition in most regions in Indonesia. The treatment should be directed to comprehensive changes of management paradigm for all aspects in it. Those were indicated by the increasing of disasters around the watershed, such as floods, droughts, landslides, erosion and increased of sediment transported by the river basin. The increasing of sedimentation which occurs in the river flow will disrupt the performance of existing hydraulic structure in the river. The event could be monitored by hydrological data, especially with the continuously and accurately of discharge and sediment data. In order to solve the problem, sediment data quality control model was needed. The purpose of this research is to determined suspended sediment data quality control model, in order to have continuous and quality guaranteed of sediment transport data. The scopes of this sediment data quality control were making criteria and sub, determining rank priority between criteria and sub, arranging scoring form, trial and error, finalization. The model consists of three main stages, there are measurement of discharge and taking sediment sample (QC1), drawing of sediment rating curve (QC2), and conversion of discharge data to sediment transport (QC3).